Protonation Equilibria of Biologically Active Ligands in Mixed Aqueous Organic Solvents - Ahmed A. El-Sherif; Mohamed M. Shoukry; Abeer T. Abd Elkarim; Mohammad H. Barakat (Bioinorganic Chemistry and Applications)
The review is mainly concerned with the protonation equilibria of biologically active ligands like amino acids, peptides, DNA constituents, and amino acid esters in nonaqueous media. Equilibrium concentrations of proton-ligand formation as a function of pH were investigated. Also, thermodynamics associated with protonation equilibria were also discussed.